Employee Performance in the Digital Age: An Analysis of the Influence of Hybrid Working, Digital Competency, Work Engagement, and Work-Life Balance on Private-Sector Employees in Jakarta - Fadhil A Putra (Publikasi Indonesia, 2026)
This research was motivated by the shift in work patterns toward flexible work arrangements, such as hybrid working, which have been increasingly adopted by companies in metropolitan cities such as Jakarta. Although hybrid working provides greater flexibility, companies continue to face challenges in maintaining consistent employee performance, particularly in work coordination, team communication, and effective performance monitoring. Furthermore, the successful implementation of hybrid working is influenced by factors such as digital competency, work engagement, and work-life balance. Previous studies have reported mixed findings regarding the relationships between these variables and employee performance. This study aimed to analyze the effects of hybrid working, digital competency, work engagement, and work-life balance on employee performance among private-sector employees in Jakarta. The study employed a quantitative approach through a survey of 250 private-sector employees who implemented hybrid working arrangements. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicated that: (1) hybrid working had a positive and significant effect on employee performance; (2) digital competency had a positive and significant effect on employee performance; (3) work engagement had a positive and significant effect on employee performance; and (4) work-life balance had a positive and significant effect on employee performance. This research contributes to the development of studies on employee performance within hybrid work environments and provides practical insights for companies in designing work policies that support employee productivity and well-being.